Tough times never last, but tough people do! - Schuller, Robert H. (Robert Harold) (Nashville T. Nelson Publishers, 1983)
A clergyman presents advice on how to build a positive self-image and work toward success.
Keywords: Success -- Religious aspects -- Christianity. Christian life -- Reformed authors. Success